دور اللجنة الإدارية المتساوية الاعضاء في تسيير المسار المهني للموظف العمومي - سميرة بن عربوة; نادية لعلايمية (My University, 2022)
In an effort to achieve democracy in the administration, Algerian legislature has established participatory bodies in the field of public service, including the Equal Membership Administrative Committee, which is an advisory body Involve the employee in the conduct of his or her career, and this right is reflected in his or her membership. An equal number of members shall be equal between the representative of the Department and the representative of the staff, thus constituting one of the staff member's important assurances The purpose of the study was to demonstrate the legal strength of the views of the Equal Membership Management Committee and its effectiveness in dealing with the cases before it. We concluded that it had an active role in the organization of personnel matters, especially those relating to disciplinary matters, since the Authority must abide by its binding views when issuing its disciplinary decision, which protects the staff member from arbitrary management ....................... ملخص المذكرة: سعيا من المشرع الجزائري لتحقيق ديمقراطية الإدارة، قام باستحداث هيئات مشاركة في مجال الوظيفة العمومية، من بينها اللجنة الإدارية المتساوية الأعضاء التي تعد هيئة استشارية الغاية منها إشراك الموظف في تسيير حياته المهنية، ويتجسد هذا الحق من خلال عضويته فيها. تضم عدد متساوي من الأعضاء يكون مناصفة بين ممثل الإدارة وممثل الموظفين، فتشكل بذلك إحدى الضمانات المهمة الممنوحة للموظف. وكان الغرض من الدراسة هو تبيان القوة القانونية لأراء اللجنة الإدارية المتساوية الأعضاء، ومدى فاعليتها في معالجة القضايا المطروحة عليها، فخلصنا أن لها دور فعال في تنظيم شؤون الموظفين خاصة ما تعلق منها بالمسائل التأديبية، إذ على السلطة التقيد بآرائها الملزمة عند إصدارها لقرارها التأديبي، وهذا حماية للموظف من تعسف الإدارة. ........................... Résumé: La législateur algérien a œuvré pour la démocratisation de l'administration par la création des instances de participation à la fonction publique y compris la commission paritaire. celle-ci est une instance consultative qui vise a impliquer le fonctionnaire dans la gestion de sa vie professionnelle, cette commission comparent nombre égal des représentants de l'administrations et des fonctionnaires et constitue ainsi l'une des garanties professionnelle accordée au fonctionnaire. L'objectif de notre étude est de démontrer le caractère obligatoire des avis de la commission administrative paritaire est son effectivité dans le traitement des affaire qui lui son soumises. l'étude conclu que ladite commission dispose d'un role effectif dans la gestion des affaires des fonctionnaires, notamment ce qui concerne les questions disciplinaires que l'administration doit se conformer a ses avis contraignants lors de son émission de sa décision disciplinaire et ce, dans le but de protéger le fonctionnaire des excès de l'administration.